1997
DOI: 10.1103/physrevlett.79.5254
|View full text |Cite
|
Sign up to set email alerts
|

3D Instability of Miscible Displacements in a Hele-Shaw Cell

Abstract: We study the downward miscible displacement of a fluid by a lighter and less viscous one in the gap of a Hele-Shaw cell. For sufficiently large velocities, a well-defined interface separates the two fluids. As long as the velocity or the viscosity ratio are below a critical value, the interface has the shape of a tongue symmetric across the gap. For viscosity ratios larger than a critical value, estimated at 1.5, there exists a critical velocity, above which the interface becomes unstable, leading to a new 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
81
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 17 publications
18
81
1
1
Order By: Relevance
“…The removal of interfacial tension allows for three dimensional (3D) structures, 'tongues' of one fluid penetrating into the other [19][20][21]24 . In regime III, the tip of the tongue is rounded as shown in the upper panel in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The removal of interfacial tension allows for three dimensional (3D) structures, 'tongues' of one fluid penetrating into the other [19][20][21]24 . In regime III, the tip of the tongue is rounded as shown in the upper panel in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the boundary coincides with a change in the 3D shape of the 'tongues' from rounded to flat fronts, as mentioned previously. Lajeunesse et al 19,20 have shown that in the limit of long times and zero diffusion, the transition between a smooth profile and a shock front is analytically predicted to occur at Z in /Z out | c ¼ 0.67. This value is higher than that observed in our experiments: Z in /Z out | c E0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies in miscible core-annular flows (Taylor 1961;Cox 1962;Chen & Meiburg 1996;Petitjeans & Maxworthy 1996;Kuang, Maxworthy & Petitjeans 2003) have focused on analysing the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating 'finger' tip. The development of different instability patterns, like axisymmetric 'corkscrew' patterns, in miscible flows has also been investigated (Lajeunesse et al 1997(Lajeunesse et al , 1999Scoffoni, Lajeunesse & Homsy 2001;Cao et al 2003;Gabard & Hulin 2003). Axisymmetric 'pearl' and 'mushroom' patterns were observed in neutrally buoyant core-annular horizontal pipe flows at high Schmidt number and Reynolds number in the range 2 < Re < 60 (d 'Olce et al 2008).…”
Section: Introductionmentioning
confidence: 99%